Inform, Invest, Incentivise: A Menu-Driven Approach to Reduce the Environmental Impact of Meat in the United States - LaBonte, Kacey; Munson, Adela; Rose, Donald (The International Journal of Sociology of Agriculture and Food, 2025)
Human food systems, especially livestock production, contribute significantly to environmental degradation. The meat industry has an outsized political influence in the United States (US) and in other countries, which makes system-level changes, such as government policies to reduce meat production and consumption, difficult to enact. In this perspective article, we propose an all-of-society approach, outlining potential actions, not just by government but also by industry and the non-profit sector, to promote sustainable diets through reduced and less impactful meat consumption. Given current political realities in the US, we argue that government incentives such as subsidies are more likely to be implemented than disincentives such as taxes. The food industry has a role to play in developing meat alternatives, in promoting new dishes focused on plant protein foods, and in reducing the impact of current meat production. The non-profit sector can contribute research and advocacy to study and promote relevant actions. In articulating this approach, we seek to enhance dialogue between food system stakeholders and to increase actions across various sectors. To this end, we provide concrete examples of such actions, organised into three broad categories, which: (1) inform the public about the environmental impacts of foods; (2) invest in alternative meats and plant protein foods; and (3) incentivise consumers, producers, and suppliers to reduce their impact by consuming, producing, and supplying more of these alternatives. We argue that this approach of simultaneous synergistic actions could ultimately lead to broader system-level change.